Prevalence of Actinobacillus actinomycetemcomitans in an ethnic adult Chinese population - Zahari, N. M.; Ismail, R.; Bunyarit SS.; Shafiei, Z.; Al Rawenduzy, K. C. M. A (Malaysian Dental Journal, 2024)
Actinobacillus actinomycetemcomitans is considered a major pathogen in periodontal disease. The aim of this study was to determine the prevalence of A. actinomycetemcomitans from 46 subjects aged 20-24 years old of who were all periodontally healthy Malays.